2012
DOI: 10.1186/1472-6963-12-99
|View full text |Cite
|
Sign up to set email alerts
|

A four-year, systems-wide intervention promoting interprofessional collaboration

Abstract: BackgroundA four-year action research study was conducted across the Australian Capital Territory health system to strengthen interprofessional collaboration (IPC) though multiple intervention activities.MethodsWe developed 272 substantial IPC intervention activities involving 2,407 face-to-face encounters with health system personnel. Staff attitudes toward IPC were surveyed yearly using Heinemann et al's Attitudes toward Health Care Teams and Parsell and Bligh's Readiness for Interprofessional Learning scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 27 publications
3
45
0
2
Order By: Relevance
“…The Attitudes Toward Health Care Teams Scale (ATHCTS) has been used in ten studies measuring attitudes towards interprofessional collaboration in a variety of settings, most commonly interprofessional education. [58][59][60][61][62][63][64][65][66][67] It consists of three subscales assessing attitudes about team value, team efficiency and the physician's shared role on the team. ATHCTS 65 The Ottawa Global Rating Scale has been used in multi-specialty education as an objective measurement of an individual's crisis resource management skills in simulated scenarios.…”
Section: Description and Validity Evidence For Teamwork Assessment Toolsmentioning
confidence: 99%
“…The Attitudes Toward Health Care Teams Scale (ATHCTS) has been used in ten studies measuring attitudes towards interprofessional collaboration in a variety of settings, most commonly interprofessional education. [58][59][60][61][62][63][64][65][66][67] It consists of three subscales assessing attitudes about team value, team efficiency and the physician's shared role on the team. ATHCTS 65 The Ottawa Global Rating Scale has been used in multi-specialty education as an objective measurement of an individual's crisis resource management skills in simulated scenarios.…”
Section: Description and Validity Evidence For Teamwork Assessment Toolsmentioning
confidence: 99%
“…‱ previous experience of IPE on attitudes to IPW and IPE In addition, Braithwaite et al, (2012;2013) found that allied health professionals (AHPs) had more positive attitudes to IPW and IPE than physicians and nurses.…”
Section: Resultsmentioning
confidence: 99%
“…Time pressures, limited resources, lack of understanding of roles and responsibilities, competing priorities, and access to other professionals prevent effective IPW between professional groups (Bailey, Jones, & Way, 2006;Braithwaite et al, 2012;Hughes & McCann, 2003;Kvarnström, 2008;Larkin & Callaghan, 2005;Snelgrove & Hughes, 2000). Healthcare teams are capable of improvising and developing strategies to work around such barriers (Baxter & Brumfit, 2008;Lingard et al, 2012).…”
Section: Directors Of Social Work 2013)mentioning
confidence: 99%
“…As outlined in Chapter 1, health-care quality and patient safety demand effective and co-ordinated leadership from politicians, 448,449 executive-level managers 81,450 and their subordinate staff -whether corporate or clinical professionals 451 -who interact with patients, directly or indirectly, 4,88,204,452,453 in the coproduction of their care. 146,155,454 Health-care leadership is, therefore, inherently distributed 30,36,455,456 and complex, 457 and necessitates active followership.…”
Section: Mortality Reviews Walkrounds and Patient Storiesmentioning
confidence: 99%